2020
DOI: 10.1186/s13063-020-04610-w
|View full text |Cite
|
Sign up to set email alerts
|

Manual therapy versus therapeutic exercise in non-specific chronic neck pain: a randomized controlled trial

Abstract: Background Nonspecific chronic neck pain is a fairly common disorder that causes a great impact, and it is greatly influenced by psychosocial factors. Among a number of treatment modalities described for its management, the most common approach is based on manual therapy and specific therapeutic exercise, which have shown a moderate effect on subjects with chronic non-specific neck pain. However, the effect times of these treatments have not been accurately detailed. Our study aims to break down a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 31 publications
1
66
1
8
Order By: Relevance
“…A classification in NDI, under moderate disability, has been shown to predict avoidance of chronic disability after whiplash in 55.7% of the patients ( Nederhand et al, 2004 ). A recent study, which compared the efficacity of manual therapy vs exercise in chronic neck pain, has shown an effect side at three months of 0.18 in the NDI, which is less than the 0.59 obtained in the current study ( Bernal-Utrera et al, 2020 ).…”
Section: Discussioncontrasting
confidence: 90%
“…A classification in NDI, under moderate disability, has been shown to predict avoidance of chronic disability after whiplash in 55.7% of the patients ( Nederhand et al, 2004 ). A recent study, which compared the efficacity of manual therapy vs exercise in chronic neck pain, has shown an effect side at three months of 0.18 in the NDI, which is less than the 0.59 obtained in the current study ( Bernal-Utrera et al, 2020 ).…”
Section: Discussioncontrasting
confidence: 90%
“…These findings suggest that the application of only one neural mobilization technique might be sufficient to improve NP in clinical practice. Hence, the time spent on manual therapy techniques could be reduced in favor of other alternative approaches, such as therapeutic exercise or therapeutic education [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that both methods reduce the pain intensity and the disability degree after 12 weeks, with therapeutic exercises having a faster effect on reduced disability degree than manual therapy [22]. Sial et al (2016) researched the effectiveness of physical therapy and home exercise programs to reduce neck discomfort in the treatment of postural neck pain.…”
Section: Discussionmentioning
confidence: 99%